Wrocław jako miejsce intensyfikacji działalności społeczno-ekonomicznej - Korenik, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Wrocław as a big city has large economic potential. It is the reason why that its role is increasing, both in the region and also in international scale. However, in order to keep this positive phenomenon in the city economy, the activities of local and regional authorities are necessary. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 48-55